The Relationship Between Intercultural Sensitivity, Ethnocentrism, Socio-Demographic Characteristics and Xenophobia in Nursing Students: A Descriptive and Multi-Centric Study - Ergezen, Fatma Dursun; Aydin, Ruveyde (Churchill Livingstone, 2025)
Background: Xenophobia plays a pivotal role in influencing the delivery of culturally competent care. Nevertheless, the relationship between intercultural sensitivity, ethnocentrism, socio-demographic characteristics and xenophobia in nursing students remains undetermined. Aim: This study aimed to determine the relationship between intercultural sensitivity, ethnocentrism, sociodemographic characteristics and xenophobia in nursing students. Methods and participants: The study involved 1045 nursing students from six universities in T & uuml;rkiye. Data were collected using the "Participant Information Form," the "Intercultural Sensitivity Scale," the "Ethnocentrism Scale," and the "Xenophobia Scale." Multiple linear regression was employed for the analysis. Results: Intercultural sensitivity ((t = -0.09; p = 0.028) emerged as a negative predictor of xenophobia levels in students, while ethnocentrism ((t = 0.17; p = 0.000) was identified as a positive predictor of xenophobia levels. Additionally, socio-demographic characteristics, including age, living in an extended family, academic year, participation in intercultural nursing courses, and interaction with immigrant neighbors, were established as significant predictors of xenophobia. Conclusion: This study revealed a direct correlation between higher intercultural sensitivity and reduced xenophobia, whereas an increase in ethnocentrism was linked to elevated levels of xenophobia. These results offer valuable insights for educators and policymakers to combat xenophobia and design targeted interventions.
Dursun Ergezen, Fatma/0000-0002-4707-060X;
Keywords: Ethnocentrism; Intercultural Sensitivity; Nursing Education; Nursing Student; Xenophobia